A prospective and observational study of clinical and functional outcome of meta carpal fracture treated with osteosynthesis using plate - Patel, Vaishvik; Shah, Sagar; Bothra, Jay S.; Desai, Sarvang M. (International Journal of Research in Orthopaedics, 2026)
Background: Metacarpal fractures are among the most common hand injuries encountered in orthopaedic practice and can significantly impair hand function if not managed appropriately. Stable fixation with early mobilization is essential for optimal functional recovery, particularly in unstable fracture patterns. Plate osteosynthesis provides rigid fixation and allows early rehabilitation, but its clinical and functional outcomes require systematic evaluation. Methods: This prospective observational study was conducted in the Department of Orthopaedics at a tertiary care centre over a defined study period. A total of 20 skeletally mature patients with closed metacarpal fractures were included. All patients underwent open reduction and internal fixation using mini-plates and screws. Patients were followed up at regular intervals for a minimum period of three months. Clinical evaluation, radiological assessment of fracture union, postoperative complications, duration of hospital stay, return to work, and functional outcomes were assessed. Functional outcome was evaluated using the Total Active Flexion (TAF) scoring system recommended by the American Society for Surgery of the Hand. Results: The majority of patients were young to middle-aged adults, with a male predominance. Transverse fractures and shaft-level involvement were the most common fracture characteristics. Radiological union was achieved within 6-7 weeks in 75% of patients. Excellent functional outcomes were observed in 75% of digits 2-5 and in all cases involving the thumb. Overall, 85% of patients achieved satisfactory functional outcomes. Most patients (70%) returned to work within 6-8 weeks. Postoperative complications were minimal, with stiffness observed in 15% of patients and infection in 5%. No cases of non-union, malunion, or implant failure were reported. Conclusions: Plate osteosynthesis is a safe and effective method for the management of metacarpal fractures, providing stable fixation, early mobilization, and excellent functional outcomes with a low complication rate. Meticulous surgical technique and structured postoperative rehabilitation play a crucial role in achieving optimal results.